Engaging European local communities in biodiversity genomics research: A five-step framework for scientists - Christian de Guttry; Chiara Bortoluzzi; Luísa S. Marins; Tinatin Chkhartishvili; Camilla R. De Pierri; Stefaniya Kamenova; Jennifer A. Leonard; Kay Lucek; Lada Lukić Bilela; Camila J. Mazzoni; Ann M. Mc Cartney; Svein-Ole Mikalsen; et al. (Biological Conservation, 2026)

Chromosomal Fusions Promote Speciation in Subterranean Blind Mole Rats - Zhuoran Kuang; Xiaojie Yang; Zachariah Gompert; Qijiao Duan; Wenyu Liu; Sanyuan Liu; Jiaqi Chen; Xiaolong Liang; Leyan Mao; Na Wan; Yinjia Wang; Zhilong Feng; et al. (Molecular Ecology, 2026)
The genomic mechanisms underlying large‐scale chromosomal rearrangements and their evolutionary consequences remain poorly understood. Here, we generated chromosome‐level genomes for two sister species pairs of blind mole rats that differ in chromosome numbers. We identified five chromosome fusions during the divergence from a common ancestor (2n = 60). Three shared fusions gave rise to the Spalax galili (2n = 52)— S. golani (2n = 54) clade and accompanied its divergence from the S. carmeli (2n = 58)— S. judaei (2n = 60) clade. Both S. galili and S. carmeli further underwent an independent fusion. These fusions, facilitated by repetitive elements, were associated with changes in three‐dimensional genome architecture. Notably, we found reduced gene flow near fusion points. Chromosomal fusions correlated with signatures of selection and may have become fixed through centromeric repeat expansion. Together, these findings provide a genome‐wide framework for investigating how chromosomal fusions relate to genome organization and lineage divergence.

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Biodiversity Genomics Research Practices Require Harmonising to Meet Stakeholder Needs in Conservation - Elena Buzan; Christian de Guttry; Chiara Bortoluzzi; Nathaniel R. Street; Kay Lucek; Anna Rosling; Lino Ometto; Alice Mouton; Luísa S. Marins; María José Ruiz‐López; José Melo‐Ferreira; Elisabet Ottosson; et al. (Molecular Ecology, 2025)
Biodiversity resilience relies on genetic diversity, which sustains the evolutionary potential of organisms in dynamic ecosystems. Genomics is a powerful tool for accurately estimating genetic diversity across genomes of species and populations. However, integration of genomic data into conservation efforts faces challenges due to the heterogeneity of approaches employed. Establishing common sets of standards for genomic data production and analysis is essential to consistently interpret results and clearly communicate outcomes to stakeholders. While the European Reference Genome Atlas (ERGA) community has contributed significantly to the standardisation of reference genome methodologies in synergy with other initiatives, there is now an urgent need to extend these principles to downstream analyses. ERGA aims to build on its experience to help establish harmonised approaches in applied biodiversity genomics research, aligned with ongoing efforts to define standardised metrics for measuring and reporting genetic diversity. Establishing consensus on best practices for genome‐wide data generation methods and applications will substantially increase accuracy, interpretability, and comparability, together with enhanced stakeholder capacities. By identifying key opportunities and challenges, as well as conducting preliminary stakeholder mapping and examining case studies, the goal is to build an inclusive framework that ensures the relevance and widespread adoption of these best practices: fostering trust and confidence in genomics research practices to meet stakeholder needs in biodiversity conservation. We call upon the broader research community to join efforts in establishing these approaches, recognising the importance of participation of end‐users, to foster the integration of genomic data into the toolkit for measuring and reporting genetic diversity.

A Genomic Update on the Evolutionary Impact of Chromosomal Rearrangements - Hannah Augustijnen; Cristina Arias‐Sardá; Marta Farré; Kay Lucek (Molecular Ecology, 2024)

Genomic hotspots of chromosome rearrangements explain conserved synteny despite high rates of chromosome evolution in a holocentric lineage - Marcial Escudero; André Marques; Kay Lucek; Andrew L. Hipp (Molecular Ecology, 2024)
Holocentric organisms, unlike typical monocentric organisms, have kinetochore activity distributed along almost the whole length of the chromosome. Because of this, chromosome rearrangements through fission and fusion are more likely to become fixed in holocentric species, which may account for the extraordinary rates of chromosome evolution that many holocentric lineages exhibit. Long blocks of genome synteny have been reported in animals with holocentric chromosomes despite high rates of chromosome rearrangements. Nothing is known from plants, however, despite the fact that holocentricity appears to have played a key role in the diversification of one of the largest angiosperm genera, Carex (Cyperaceae). In the current study, we compared genomes of Carex species and a distantly related Cyperaceae species to characterize conserved and rearranged genome regions. Our analyses span divergence times ranging between 2 and 50 million years. We also compared a C. scoparia chromosome‐level genome assembly with a linkage map of the same species to study rearrangements at a population level and suppression of recombination patterns. We found longer genome synteny blocks than expected under a null model of random rearrangement breakpoints, even between very distantly related species. We also found repetitive DNA to be non‐randomly associated with holocentromeres and rearranged regions of the genome. The evidence of conserved synteny in sedges despite high rates of chromosome fission and fusion suggests that conserved genomic hotspots of chromosome evolution related to repetitive DNA shape the evolution of recombination, gene order and crossability in sedges. This finding may help explain why sedges are able to maintain species cohesion even in the face of high interspecific chromosome rearrangements.

Holocentric repeat landscapes: From micro‐evolutionary patterns to macro‐evolutionary associations with karyotype evolution - Camille Cornet; Pablo Mora; Hannah Augustijnen; Petr Nguyen; Marcial Escudero; Kay Lucek (Molecular Ecology, 2024)
Repetitive elements can cause large‐scale chromosomal rearrangements, for example through ectopic recombination, potentially promoting reproductive isolation and speciation. Species with holocentric chromosomes, that lack a localized centromere, might be more likely to retain chromosomal rearrangements that lead to karyotype changes such as fusions and fissions. This is because chromosome segregation during cell division should be less affected than in organisms with a localized centromere. The relationships between repetitive elements and chromosomal rearrangements and how they may translate to patterns of speciation in holocentric organisms are though poorly understood. Here, we use a reference‐free approach based on low‐coverage short‐read sequencing data to characterize the repeat landscape of two independently evolved holocentric groups: Erebia butterflies and Carex sedges. We consider both micro‐ and macro‐evolutionary scales to investigate the repeat landscape differentiation between Erebia populations and the association between repeats and karyotype changes in a phylogenetic framework for both Erebia and Carex . At a micro‐evolutionary scale, we found population differentiation in repeat landscape that increases with overall intraspecific genetic differentiation among four Erebia species. At a macro‐evolutionary scale, we found indications for an association between repetitive elements and karyotype changes along both Erebia and Carex phylogenies. Altogether, our results suggest that repetitive elements are associated with the level of population differentiation and chromosomal rearrangements in holocentric clades and therefore likely play a role in adaptation and potentially species diversification.

Beyond gene flow: (non)‐parallelism of secondary contact in a pair of highly differentiated sibling species - Hannah Augustijnen; Kay Lucek (Molecular Ecology, 2024)
Replicated secondary contact zones can provide insights into the barriers to gene flow that are important during speciation and can reveal to which degree secondary contact may result in similar evolutionary outcomes. Here, we studied two secondary contact zones between highly differentiated Alpine butterflies of the genus Erebia using whole‐genome resequencing data. We assessed the genomic relationships between populations and species and found hybridization to be rare, with no to little current or historical introgression in either contact zone. There are large similarities between contact zones, consistent with an allopatric origin of interspecific differentiation, with no indications for ongoing reinforcing selection. Consistent with expected reduced effective population size, we further find that scaffolds related to the Z‐chromosome show increased differentiation compared to the already high levels across the entire genome, which could also hint towards a contribution of the Z chromosome to species divergence in this system. Finally, we detected the presence of the endosymbiont Wolbachia , which can cause reproductive isolation between its hosts, in all E. cassioides , while it appears to be fully or largely absent in contact zone populations of E. tyndarus . We discuss how this rare pattern may have arisen and how it may have affected the dynamics of speciation upon secondary contact.

Towards a genomic resolution of the Phengaris alcon species complex - Kay Lucek; Lucas Blattner; Camille Cornet; Yannick Chittaro; Andreas Erhardt; Andreas Jaun; Bernhard Jost; Nathalie Winiger; Hans-Peter Wymann; Goran Dušej (Conservation Genetics, 2024)
Taxonomic entities below the species level often pose difficulties for conservation practice, especially when they are ecologically distinct from the nominal species. Genomic tools provide the opportunity to study and potentially resolve such cryptic diversity. The Alcon blue butterfly Phengaris alcon species complex is such a cryptic example, comprising different ecotypes or even subspecies, one of them is the high elevation taxon P. rebeli from the European Alps. We sequenced a first reference genome for Phengaris alcon . Furthermore, we generated whole genome resequence data for individuals of three Swiss ecotypes, i.e., the low elevation P. alcon , the mid elevation and high elevation alpine P. rebeli and integrated genomic data from across Europe to study the relationship among these ecotypes. At a European scale, our results suggest that for the P. alcon complex, biogeography and the evolutionary context of diversification is more multifaceted than previously suggested, falling in the range of more recent ecological speciation. In Switzerland, the three ecotypes were genetically isolated with only limited current gene flow between them. Past gene flow, however, could have given rise to the mid elevation ecotype. Our findings emphasise that high elevation P. rebeli in the Alps should be treated as a distinct species. Our study highlights how the availability of reference genome assemblies allows to address so far open taxonomic questions in conservation research and that broadscale studies are needed to understand the biogeographic history of apparent diversification.

Genomic evidence for three distinct species in the Erebia manto complex in Central Europe (Lepidoptera, Nymphalidae) - Amanda Jospin; Yannick Chittaro; Daniel Bolt; David Demergès; Kevin Gurcel; Jürgen Hensle; Andreas Sanchez; Christophe Praz; Kay Lucek (Conservation Genetics, 2023)
A problem to implement conservation strategies is that in many cases recognized taxa are in fact complexes of several cryptic species. Failure to properly delineate species may lead to misplaced priorities or to inadequate conservation measures. One such species complex is the yellow-spotted ringlet Erebia manto , which comprises several phenotypically distinct lineages, whose degree of genomic isolation has so far not been assessed. Some of these lineages are geographically restricted and thus possibly represent distinct units with conservation priorities. Using several thousand nuclear genomic markers, we evaluated to which degree the bubastis lineage from the Alps and the vogesiaca lineage from the Vosges, are genetically isolated from the widespread manto lineage. Our results suggest that both lineages are genetically as strongly differentiated from manto as other taxonomically well separated sibling species in this genus from each other, supporting a delineation of bubastis and vogesiaca as independent species. Given the restricted and isolated range of vogesiaca as well as the disjunct distribution of bubastis, our findings have significant implication for future conservation efforts on these formerly cryptic species and highlight the need to investigate the genomic identity within species complexes.

Lineage‐specific adaptation to climate involves flowering time in North American Arabidopsis lyrata - Nora Walden; Kay Lucek; Yvonne Willi (Molecular Ecology, 2020)
Adaptation to local climatic conditions is commonly found within species, but whether it involves the same intraspecific genomic variants is unknown. We studied this question in North American Arabidopsis lyrata , whose current distribution is shaped by post‐glacial range expansion from two refugia, resulting in two distinct genetic clusters covering comparable climatic gradients. Using pooled whole‐genome sequence data of 41 outcrossing populations, we identified loci associated with three niche‐determining climatic variables in the two clusters and compared these outliers. Little evidence was found for parallelism in climate adaptation for single nucleotide polymorphisms (SNPs) and for genes with an accumulation of outlier SNPs. Significantly increased selection coefficients supported them as candidates of climate adaptation. However, the fraction of gene ontology (GO) terms shared between clusters was higher compared to outlier SNPs and outlier genes, suggesting that selection acts on similar pathways but not necessarily the same genes. Enriched GO terms involved responses to abiotic and biotic stress, circadian rhythm and development, with flower development and reproduction being among the most frequently detected. In line with GO enrichment, regulators of flowering time were detected as outlier genes. Our results suggest that while adaptation to environmental gradients on the genomic level are lineage‐specific in A. lyrata , similar biological processes seem to be involved. Differential loss of standing genetic variation, probably driven by genetic drift, can in part account for the lack of parallel evolution on the genomic level.

Recent sympatric speciation involving habitat-associated nuptial colour polymorphism in a crater lake cichlid - Melissa Lemoine; Marta Barluenga; Kay Lucek; Salome Mwaiko; Marcel Haesler; Lauren J. Chapman; Colin A. Chapman; Ole Seehausen (Hydrobiologia, 2019)

The role of structural genomic variants in population differentiation and ecotype formation in Timema cristinae walking sticks - Kay Lucek; Zachariah Gompert; Patrik Nosil (Molecular Ecology, 2019)
Theory predicts that structural genomic variants such as inversions can promote adaptive diversification and speciation. Despite increasing empirical evidence that adaptive divergence can be triggered by one or a few large inversions, the degree to which widespread genomic regions under divergent selection are associated with structural variants remains unclear. Here we test for an association between structural variants and genomic regions that underlie parallel host‐plant‐associated ecotype formation in Timema cristinae stick insects. Using mate‐pair resequencing of 20 new whole genomes we find that moderately sized structural variants such as inversions, deletions and duplications are widespread across the genome, being retained as standing variation within and among populations. Using 160 previously published, standard‐orientation whole genome sequences we find little to no evidence that the DNA sequences within inversions exhibit accentuated differentiation between ecotypes. In contrast, a formerly described large region of reduced recombination that harbours genes controlling colour‐pattern exhibits evidence for accentuated differentiation between ecotypes, which is consistent with differences in the frequency of colour‐pattern morphs between host‐associated ecotypes. Our results suggest that some types of structural variants (e.g., large inversions) are more likely to underlie adaptive divergence than others, and that structural variants are not required for subtle yet genome‐wide genetic differentiation with gene flow.

Postglacial ecotype formation under outcrossing and self‐fertilization in Arabidopsis lyrata - Kay Lucek; Nora Hohmann; Yvonne Willi (Molecular Ecology, 2019)
The formation of ecotypes has been invoked as an important driver of postglacial biodiversity, because many species colonized heterogeneous habitats and experienced divergent selection. Ecotype formation has been predominantly studied in outcrossing taxa, while far less attention has been paid to the implications of mating system shifts. Here, we addressed whether substrate‐related ecotypes exist in selfing and outcrossing populations of Arabidopsis lyrata subsp. lyrata and whether the genomic footprint differs between mating systems. The North American subspecies colonized both rocky and sandy habitats during postglacial range expansion and shifted the mating system from predominantly outcrossing to predominantly selfing in a number of regions. We performed an association study on pooled whole‐genome sequence data of 20 selfing or outcrossing populations, which suggested genes involved in adaptation to substrate. Motivated by enriched gene ontology terms, we compared root growth between plants from the two substrates in a common environment and found that plants originating from sand grew roots faster and produced more side roots, independent of mating system. Furthermore, single nucleotide polymorphisms associated with substrate‐related ecotypes were more clustered among selfing populations. Our study provides evidence for substrate‐related ecotypes in A. lyrata and divergence in the genomic footprint between mating systems. The latter is the likely result of selfing populations having experienced divergent selection on larger genomic regions due to higher genome‐wide linkage disequilibrium.

On the Status of Threespine Stickleback (Gasterosteus aculeatus Linnaeus 1758) in Lake Bracciano, Italy - Sakshi Sharda; Emmanuelle Argenti; Kay Lucek (Fishes, 2018)
For many species, the Mediterranean region harbors distinct lineages that are of conservation concerns. However, many of these are threatened by habitat degradation and by the introduction of non-native species. Here, we assess the status of the native threespine stickleback (Gasterosteus aculeatus) in the Lake Bracciano region in Italy, where stickleback have been historically present. During a dedicated sampling campaign in summer 2015, surveying the potential habitats that sticklebacks commonly occupy, we could not confirm the presence of this species but found introduced species to be often most abundant. Stickleback are thus likely to either have become extinct over the last decades or be on the verge to extinction in the Lake Bracciano region.

Long‐term balancing selection on chromosomal variants associated with crypsis in a stick insect - Dorothea Lindtke; Kay Lucek; Víctor Soria‐Carrasco; Romain Villoutreix; Timothy E. Farkas; Rüdiger Riesch; Stuart R. Dennis; Zach Gompert; Patrik Nosil (Molecular Ecology, 2017)
How polymorphisms are maintained within populations over long periods of time remains debated, because genetic drift and various forms of selection are expected to reduce variation. Here, we study the genetic architecture and maintenance of phenotypic morphs that confer crypsis in Timema cristinae stick insects, combining phenotypic information and genotyping‐by‐sequencing data from 1,360 samples across 21 populations. We find two highly divergent chromosomal variants that span megabases of sequence and are associated with colour polymorphism. We show that these variants exhibit strongly reduced effective recombination, are geographically widespread and probably diverged millions of generations ago. We detect heterokaryotype excess and signs of balancing selection acting on these variants through the species’ history. A third chromosomal variant in the same genomic region likely evolved more recently from one of the two colour variants and is associated with dorsal pattern polymorphism. Our results suggest that large‐scale genetic variation associated with crypsis has been maintained for long periods of time by potentially complex processes of balancing selection.

Effects of interspecific gene flow on the phenotypic variance–covariance matrix in Lake Victoria Cichlids - Kay Lucek; Lucie Greuter; Oliver M. Selz; Ole Seehausen (Hydrobiologia, 2017)

Genomic landscape of early ecological speciation initiated by selection on nuptial colour - David Alexander Marques; Kay Lucek; Marcel Philipp Haesler; Anna Fiona Feller; Joana Isabel Meier; Catherine E. Wagner; Laurent Excoffier; Ole Seehausen (Molecular Ecology, 2017)
Ecological speciation is the evolution of reproductive isolation as a consequence of direct divergent natural selection or ecologically mediated divergent sexual selection. While the genomic signature of the former has been extensively studied in recent years, only few examples exist for genomic differentiation where environment‐dependent sexual selection has played an important role. Here, we describe a very young (~90 years old) population of threespine sticklebacks exhibiting phenotypic and genomic differentiation between two habitats within the same pond. We show that differentiation among habitats is limited to male throat colour and nest type, traits known to be subject to sexual selection. Divergence in these traits mirrors divergence in much older benthic and limnetic stickleback species pairs from North American west coast lakes, which also occur in sympatry but are strongly reproductively isolated from each other. We demonstrate that in our population, differences in throat colour and breeding have been stable over a decade, but in contrast to North American benthic and limnetic stickleback species, these mating trait differences are not accompanied by divergence in morphology related to feeding, predator defence or swimming performance. Using genomewide SNP data, we find multiple genomic islands with moderate differentiation spread across several chromosomes, whereas the rest of the genome is undifferentiated. The islands contain potential candidate genes involved in visual perception of colour. Our results suggest that phenotypic and multichromosome genomic divergence of these morphs was driven by environment‐dependent sexual selection, demonstrating incipient speciation after only a few decades of divergence in sympatry.

Cryptic invasion drives phenotypic changes in central European threespine stickleback - Kay Lucek (Conservation Genetics, 2016)

Distinctive insular forms of threespine stickleback (Gasterosteus aculeatus) from western Mediterranean islands - Kay Lucek; Ole Seehausen (Conservation Genetics, 2015)

Hybrid ‘superswarm’ leads to rapid divergence and establishment of populations during a biological invasion - Denis Roy; Kay Lucek; Ryan P. Walter; Ole Seehausen (Molecular Ecology, 2015)
Understanding the genetic background of invading species can be crucial information clarifying why they become invasive. Intraspecific genetic admixture among lineages separated in the native ranges may promote the rate and extent of an invasion by substantially increasing standing genetic variation. Here, we examined the genetic relationships among threespine stickleback that recently colonized Switzerland. This invasion results from several distinct genetic lineages that colonized multiple locations and have since undergone range expansions, where they coexist and admix in parts of their range. Using 17 microsatellites genotyped for 634 individuals collected from 17 Swiss and two non‐Swiss European sites, we reconstruct the invasion of stickleback and investigate the potential and extent of admixture and hybridization among the colonizing lineages from a population genetic perspective. Specifically, we test for an increase in standing genetic variation in populations where multiple lineages coexist. We find strong evidence of massive hybridization early on, followed by what appears to be recent increased genetic isolation and the formation of several new genetically distinguishable populations, consistent with a hybrid ‘superswarm’. This massive hybridization and population formation event(s) occurred over approximately 140 years and likely fuelled the successful invasion of a diverse range of habitats. The implications are that multiple colonizations coupled with hybridization can lead to the formation of new stable genetic populations potentially kick‐starting speciation and adaptive radiation over a very short timescale.

Little evidence for a selective advantage of armour-reduced threespined stickleback individuals in an invertebrate predation experiment - Michael Zeller; Kay Lucek; Marcel Haesler; Ole Seehausen; Arjun Sivasundar (Evolutionary Ecology, 2012)

Hybridization between distant lineages increases adaptive variation during a biological invasion: stickleback in Switzerland - KAY LUCEK; DENIS ROY; ETIENNE BEZAULT; ARJUN SIVASUNDAR; OLE SEEHAUSEN (Molecular Ecology, 2010)
The three‐spined stickleback is a widespread Holarctic species complex that radiated from the sea into freshwaters after the retreat of the Pleistocene ice sheets. In Switzerland, sticklebacks were absent with the exception of the far northwest, but different introduced populations have expanded to occupy a wide range of habitats since the late 19th century. A well‐studied adaptive phenotypic trait in sticklebacks is the number of lateral plates. With few exceptions, freshwater and marine populations in Europe are fixed for either the low plated phenotype or the fully plated phenotype, respectively. Switzerland, in contrast, harbours in close proximity the full range of phenotypic variation known from across the continent. We addressed the phylogeographic origins of Swiss sticklebacks using mitochondrial partial cytochrome b and control region sequences. We found only five different haplotypes but these originated from three distinct European regions, fixed for different plate phenotypes. These lineages occur largely in isolation at opposite ends of Switzerland, but co‐occur in a large central part. Across the country, we found a strong correlation between a microsatellite linked to the high plate ectodysplasin allele and the mitochondrial haplotype from a region where the fully plated phenotype is fixed. Phylogenomic and population genomic analysis of 481 polymorphic amplified fragment length polymorphism loci indicate genetic admixture in the central part of the country. The same part of the country also carries elevated within‐population phenotypic variation. We conclude that during the recent invasive range expansion of sticklebacks in Switzerland, adaptive and neutral between‐population genetic variation was converted into within‐population variation, raising the possibility that hybridization between colonizing lineages contributed to the ecological success of sticklebacks in Switzerland.